(untitled) (Plant Tissue Culture and Biotechnology, 2025)
For ex situ conservation, Eulophia graminea, a terrestrial orchid, can be micro-propagated on MS medium supplemented with different concentrations and combinations of plant growth regulators (PGRs), auxins (IAA, IBA, NAA, Picloram) and cytokinins (BAP, Kn) to produce MSBs or PLBs from in vitro grown rhizome and leaf segments of germinated plantlets accordingly. In the case of rhizome segments, organogenesis occurred on MS medium supplemented with 3.0 mg/l BAP and 1.5 mg/l NAA producing the highest percentage of MSBs per segment. The average number of induced MSBs was 7.8 ± 0.58 and the rate was 89.33 ± 1.96 percent within the minimum required time of 4.42 ± 0.10 weeks. However, embryogenesis took place in the leaf segment and the MS medium supplemented with 3.0 mg/l BAP and 1.5 mg/l Picloram produced the prime percentage of greenish PLBs. The maximum rate was 78.67 ± 2.24 percent in the shortest amount of time, which was 5.36 ± 0.09 weeks. Following 30 days of mini shoot bud culture, the maximum elongation rate on liquid conditions was 4.23 ± 0.04 cm, whereas the maximum rate on semi-solid media was 4.17 ± 0.03 cm. MS supplemented with 2.0 mg/l BAP and 1.2 mg/l NAA was found to be best for semi-solid and liquid cultures for the growth and elongation of MSBs from rhizome segments. MS supplemented with 1.0 mg/l IBA and 1.0 mg/l NAA was best for root induction and development. The length of the roots was 3.76 ± 0.04 cm and the number of roots per seedling was 5.00 ± 0.28. After successive phases of acclimatization hardened seedlings were transferred to the outside condition and the survival rate was 74.29%. Plant Tissue Cult. & Biotech. 35(1): 141-153, 2025 (June)